From Page to Post: Literature in the Age of Social Media - Sneha Anantpur (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2026)
This paper examines the evolving relationship between literature and social media, exploring how digital platforms have transformed literary production, form, and readership. By analyzing the rise of Instapoetry, Twitter fiction, BookTok communities, and fan-fiction platforms, it argues that social media functions as both a literary space and a participatory medium where authorship is democratized and reader engagement is heightened. The paper highlights how brevity, interactivity, and visuality have redefined literary aesthetics while also raising concerns about commodification, algorithm-driven creativity, and the dilution of depth. Drawing upon case studies and critical perspectives, it positions social media as neither the decline of literature nor a mere supplement, but as an emergent literary ecosystem that reconfigures traditional notions of authorship, readership, and form. Ultimately, the paper suggests that the shift from page to post signifies not a rupture but a continuity of literature’s adaptive resilience in the digital age.